MANAJEMEN PELAYANAN PRIMA UNTUK MENINGKATKAN DAYA SAING EKONOMI KREATIF DI KELURAHAN PULAU PANGGANG, KEPULAUAN SERIBU DKI JAKARTA - Dewi, Desilia Purnama; Zubaidah, Siti; Sugiyarto, Sugiyarto; Suminar, Ratna; Sarah, Nani Nuraeni (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The village of Pulau Panggang is one of the cities of the North Thousand Islands, Keep Kepulauan Seribu Regency, Jakarta, Indonesia. This island has only hiking trails and has not made much development clearly visible.The island has a population of 6,319 inhabitants (2018 census), the majority of people with low to medium incomes based on tourism considerations. The local population cannot thrive on the existence of hotels on this island. Pulai's economic wheels spin after the arrival of foreign tourists and locals / residents of Jakarta on vacation at the weekend.In addition, his second income is trade, bringing food / clothing from Jakarta and selling it on Panggang Island and the next largest island, Pramuka Island.Seeing the ups and downs of their economy, teachers in the D-III Study Program at the Pamulang University Secretariat felt compelled to help residents of Panggang Island solve their problems. We will combine traditional ways of doing business in the communications sciences business, which refer to excellent services, so that they can change their paradigms about the concept of trade, in order to increase the competitiveness of the creative economy, which in turn will increase. your income.